Organized Recess as a Strategy to Improve Physical Activity Levels and Physical Condition in Adolescents [Recreo Organizado Como Estrategia Para Mejorar Los Niveles Actividad Física y Condición Física en Adolescentes Escolares] - De Moraes-Ferrari, G (Federacion Espanola de Docentes de Educacion Fisica, 2021)
The purpose of this project was to identify the effects of an intervention during school recesses on physical condition and physical activity in Chilean adolescents. Fifty volunteer students (27 girls) participated, with an average of 14.2 ± 1.3 years. Control group (n=21) and intervention group (n=29). Targeted activities were carried out in the schoolyard during the two recesses in the morning, for 12 weeks. Pre and post test, the 20m shuttle run test, manual dynamometry, body composition, PAQ-A questionnaire and accelerometry were evaluated. The intervention group (GI), had better levels of physical activity than the control group (GC), during recess, physical education class, lunch time and steps/day (p <0.05). In conclusion, the active participation during recesses can increase minutes of moderate-vigorous physical activity and improve cardiorespiratory fitness. © Copyright: Federación Española de Asociaciones de Docentes de Educación Física (FEADEF).